Efficacy and safety of once-weekly insulin icodec compared to once-daily insulin g U-100 in patients with type II diabetes: a systematic review and meta-analysis - Syed Zia Saleem; Areeba Fareed; Syed Muhammad Muneeb Akhtar; Solay Farhat; Amira Mohamed Taha; Aymar Akilimali (Diabetology & Metabolic Syndrome, 2024)
Abstract Background//Objective Diabetes affects millions of people globally, despite treatment options, adherence and other factors pose obstacles. Once-weekly Insulin Icodec, a novel basal Insulin analog with a week-long half-life, offers potential benefits, enhancing convenience, adherence, and quality of life for improved glycemic control. This systematic review and meta-analysis aimed to assess the efficacy and safety of once-weekly Insulin Icodec compared to once-daily Insulin Glargine U-100 in individuals with type II diabetes (T2D). Methods A comprehensive literature search was conducted using PubMed, and Cochrane Library databases before September 2023 to identify relevant Randomized control trials (RCTs) with no language restrictions following PRISMA guidelines. The Cochrane risk-of-bias tool was used for quality assessment. All statistical analyses were conducted using RevMan (version 5.4; Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, 2014). Result Four RCTs published from 2020 to 2023 with a cumulative sample size of 1035 were included. The pooled mean difference (MD) revealed a 4.68% longer TIR (%) with Insulin Icodec compared to Insulin Glargine U-100 [{95% CI (0.69, 8.68), p = 0.02}], the estimated mean changes in HbA1c (%) and FPG (mg%) were found to be insignificant between the two groups [MD = − 0.12 {95% CI (− 0.26, 0.01), p = 0.07}] and [MD = − 2.59 {95% CI (− 6.95, 1.78), p = 0.25}], respectively. The overall OR for hypoglycemia was also nonsignificant between the two regimens 1.04 [{95% CI (0.71, 1.52), p = 0.84}]. Other safety parameters were similar between the two groups. Conclusions Switching from daily Insulin Glargine U-100 to weekly Insulin Icodec showed longer TIR (%) as well as similar blood glycemic control and safety profile. Hence, it may be a good alternate option for management of longstanding T2D.